Proteasome localization and activity in pig brain and in vivo small molecule screening for activators - Amrein Almira, Adriana; Chen, May W.; El Demerdash, Nagat; Javdan, Cameron; Park, Dongseok; Lee, Jennifer K.; Martin, Lee J. (Frontiers in Cellular Neuroscience, 2024)
Loss of proteasome function, proteinopathy, and proteotoxicity may cause neurodegeneration across the human lifespan in several forms of brain injury and disease. Drugs that activate brain proteasomes in vivo could thus have broad therapeutic impact in neurology. Using pigs, a clinically relevant large animal with a functionally compartmental gyrencephalic cerebral cortex, we evaluated the localization and biochemical activity of brain proteasomes and tested the ability of small molecules to activate brain proteasomes. By western blotting, proteasome protein subunit PSMB5 and PSMA3 levels were similar in different pig brain regions. Immunohistochemistry for PSMB5 showed localization in the cytoplasm (diffuse and particulate) and nucleus (cytoplasm